Digital Humanism - Ludger Hagedorn; Ute Schmid; Susan Winter; Stefan Woltran (Springer Nature Switzerland, 2026)
This open access volume constitutes the proceedings of First Interdisciplinary Science and Research Conference on Digital Humanism, DIGHUM 2025, Vienna, Austria, during November 20–21, 2025. The 30 full papers and 12 short papers included in this book were carefully reviewed and selected from 98 submissions. They were organized in topical sections as follows: 1) Digital Humanism Reshaping Computer Science, 2) Digital Humanism: Ethical and Legal Aspects, 3) Digital Humanism in Political and Social Sciences, and 4) Breaking Interdisciplinary Silos: Digital Humanism Across Disciplines.